PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP FIRM VALUE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2018-2020 - Christine, Christine; Santioso, Linda (Jurnal Paradigma Akuntansi, 2024)
In this research, aims to determine the effect of the leverage, liquidity, profitability and also dividend policy on firm value of manufacturing companies during 2018-2020. For the sample used was purposive sampling method and amounted data valid were in 33 companies, those are listed on the Indonesia Stock Exchanged (IDX). The data processing technique uses applications program by the E-views 12. The final research of this study indicate that liquidity and dividend policy does not have effect of firm value, but its different with leverage and profitability have a significant and positive effect on firm value. This information will be useful for company, researcher, and investors who is choosing investments to pay more attention to the factors that affect the firm value’s in the long terms nor short terms.